2015
DOI: 10.1007/s40620-015-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

How to balance risks and benefits in the management of CKD patients with coronary artery disease

Abstract: Chronic kidney disease (CKD) is associated with a high burden of coronary artery disease (CAD), which remains the most common cause of morbidity and mortality in CKD patients. Although the management of CAD is more challenging in patients with CKD than in the general population, and coupled with concerns about further deterioration of renal function and therapy-related toxic effects, CKD patients and those receiving dialysis have not traditionally been included in randomized trials evaluating either medical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 87 publications
1
18
0
3
Order By: Relevance
“…Percutaneous coronary revascularization improves long-term survival when compared with medical therapy, 9 yet we found that ESRD patients on HD were getting less catheterization than the other two groups (45.6% vs 75.8% and 93.9%) (P,0.001). Unique risk factors were present in these patients putting them at once at high risk of CAD and of procedural complications.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Percutaneous coronary revascularization improves long-term survival when compared with medical therapy, 9 yet we found that ESRD patients on HD were getting less catheterization than the other two groups (45.6% vs 75.8% and 93.9%) (P,0.001). Unique risk factors were present in these patients putting them at once at high risk of CAD and of procedural complications.…”
Section: Discussionmentioning
confidence: 62%
“…However, detailed reports including length of stay, differences in utilization of current evidence-based medical management, and invasive coronary intervention including coronary bypass surgery are not available on CKD and ESRD patients regarding CAD treatment. 9 Many observations have reported discrimination of care for patients with CKD; studies showed that CKD patients were less likely to receive evidence-based therapy in ACS compared with patients without CKD as they are considered suboptimal candidates for aggressive management of their cardiac disease. 2,9 In our study, the exclusion criterion of AKI regardless of the presence of prior CKD was used to eliminate bias regarding the administration or withholding medication, intervention, and the length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations